SPE Offshore Europe Conference &Amp; Exhibition 2021
DOI: 10.2118/205404-ms
|View full text |Cite
|
Sign up to set email alerts
|

EM-Based 2D Corrosion Azimuthal Imaging using Physics Informed Machine Learning PIML

Abstract: In the wake of today's industrial revolution, many advanced technologies and techniques have been developed to address the complex challenges in well integrity evaluation. One of the most prominent innovations is the integration of physics-based data science for robust downhole measurements. This paper introduces a promising breakthrough in electromagnetism-based corrosion imaging using physics informed machine learning (PIML), tested and validated on the cross-sections of real metal casings/tubing with defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As the partial derivatives from the loss function pass through many layers, their values gradually decreases to zero. It is shown in a previous study (Ooi et al 2021) that the training process of mapping EM readings to cross-sectional image pixels suffers from the vanishing gradient problem. In addition, the study has shown that the performance of typical fully-connected neural networks stops improving after a certain amount of layers have been added to the network, and begins to decrease with additional layers.…”
Section: Hybrid Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…As the partial derivatives from the loss function pass through many layers, their values gradually decreases to zero. It is shown in a previous study (Ooi et al 2021) that the training process of mapping EM readings to cross-sectional image pixels suffers from the vanishing gradient problem. In addition, the study has shown that the performance of typical fully-connected neural networks stops improving after a certain amount of layers have been added to the network, and begins to decrease with additional layers.…”
Section: Hybrid Neural Networkmentioning
confidence: 99%
“…The LSTM network is vital in preventing this problem by using consecutive layers of gates in each of its cells to throttle the "memory" of partial derivative values to keep at each cell. The formulations of the LSTM layer for EM inspection is detailed in (Ooi et al 2021).…”
Section: Hybrid Neural Networkmentioning
confidence: 99%